The effect of extreme weather events on child nutrition and health - Emily Injete Amondo; Emmanuel Nshakira-Rukundo; Alisher Mirzabaev (Food Security, 2023)
This study traces the causal effects of extreme weather events on nutritional and health outcomes among rural children in Uganda using four waves of individual child survey data (2009–2014). A simultaneous regression model was applied for causal inference while also accounting for households' adaptive responses. The study finds the evidence of a significant negative relationship between extreme weather events and availability of calories and nutrients for children. In particular, droughts reduced calorie, protein and zinc supply, and overall diet diversity by 67%, 37%, 28% and 30%, respectively. We further traced the effects of this reduced calorie and nutrient availability on child health indicators. A 10% decrease in zinc supply decreased height-for-age z-scores (HAZ) by around 0.139 - 0.164 standard deviations (SD), and increased probability of stunting ranging from 3.1 to 3.5 percentage points. Both boys and girls HAZ and stunting rates were sensitive to nutrient inadequacies. Different coping and adaptation strategies significantly influenced rural households' ability to safeguard children's nutrition and health against the effects of extreme weather. The findings of this study provide specific insights for building ex-ante resilience against extreme weather events, particularly when compared to ex-post, unsustainable, and often costlier relief actions.
Keywords: O13; Q54; I15; C3; 630; Nutrition; Child stunting; Droughts; Heat waves; Zinc; Livestock